2005
DOI: 10.1093/ije/dyh394
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of childhood and adult socioeconomic position to adult obesity and smoking behaviour: an international comparison

Abstract: As expected, adult SEP was an important influence on smoking behaviour and obesity. In addition, factors related to disadvantaged social origins appeared to increase the risk of obesity and reduce the probability of quitting smoking in adulthood, particularly in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
142
4
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(167 citation statements)
references
References 41 publications
14
142
4
7
Order By: Relevance
“…A recent examination of seven population based studies found robust associations of childhood socioeconomic position with adult obesity across the cohorts in females, but weaker and less consistent associations in males. 25 Thus, it appears that early life characteristics related to socioeconomic position and educational attainment have a greater effect on female adult BMI than they do on male adult BMI. These sex differences may be due to chance or could be due to sex differences in some of the pathways that link childhood socioeconomic position and education to adult BMI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent examination of seven population based studies found robust associations of childhood socioeconomic position with adult obesity across the cohorts in females, but weaker and less consistent associations in males. 25 Thus, it appears that early life characteristics related to socioeconomic position and educational attainment have a greater effect on female adult BMI than they do on male adult BMI. These sex differences may be due to chance or could be due to sex differences in some of the pathways that link childhood socioeconomic position and education to adult BMI.…”
Section: Discussionmentioning
confidence: 99%
“…219 Socioeconomic gradients exist for multiple health behaviors over the life course, and the combination of several unhealthy behaviors adds up to explain a large part of the socioeconomic health gap. Smoking, poor diet, inactivity, obesity, and medication nonadherence tend to be more prevalent among individuals of low SEP. [220][221][222][223][224][225] Furthermore, SEP in childhood helps account for unhealthy behaviors and health risk in the adult years. For example, a British cohort study that followed up subjects from birth to 66 years of age found that both childhood and adult SEP (ie, father's occupational class and mother's education) accounted for a significant portion of health inequalities in mortality risk by shaping exposure to smoking and other risk behaviors.…”
Section: Behavioral Mechanismsmentioning
confidence: 99%
“…body mass index, smoking) and, while these have been previously associated with pain Hildebrandt et al, 2000;John et al, 2006), it is unlikely that these would be limited to persons with disabling, but not non-disabling, pain. Social class is a strong marker of both body mass index and smoking status (Power et al, 2005) and, therefore, adjusting for social class will have controlled, in part, for the effect of these two potential confounders and such adjustment had little impact on the results. Thus, while one cannot rule out residual confounding, we consider it unlikely that the omission of these factors will have had a major impact on the findings.…”
Section: Differences Between Men and Womenmentioning
confidence: 99%